Consumer awareness towards promotional strategies implemented by FAMA in Melaka / Mohd Shafiq Mohamad Jaapar - Mohamad Jaapar, Mohd Shafiq (Faculty of Business and Management, 2008)
The purpose of this research is to know the consumers respondent whether they are noticeable and aware about the promotional strategies that implemented by FAMA in Melaka state. The promotional strategies consist of elements such as advertising, personal selling, public relations and sale promotions. Nowadays promotional strategies have gained importance within the country to achieving the competitive advantage. Moreover promotional strategies have been used not by the profit organization but also the nonprofit organization.